A method for in-situ growth of boride and oxide nanoparticles on carbon fiber
By growing boride and oxide nanoparticles in situ on carbon fibers, the problems of uneven distribution of nanoparticles and large ceramic powder size in the prior art are solved, and the performance improvement of carbon fiber composite materials is achieved.
Patent Information
- Application Number
- CN202310532599.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-12
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-05-12
AI Technical Summary
When the prior art introduces boronide nanoparticles into carbon fibers, the distribution is uneven and the ceramic powder used is large in size, which affects the performance of the composite fiber material.
By growing boride and oxide nanoparticles in situ on carbon fibers, electrospinning liquid is prepared using boric acid, sorbitol, zirconium n-propanol/hafnium n-propanol and polyvinylpyrrolidone as raw materials. After pre-oxidation and calcination under a mixture of argon and oxygen, uniform distribution and growth of nanoparticles are achieved.
The uniform distribution of boride and oxide nanoparticles is achieved, the ablation resistance, oxidation resistance and thermal expansion coefficient of carbon fiber are improved, and the overall performance of the composite material is enhanced.
Smart Images

Figure CN116411368B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite fibers, and in particular relates to a method for in-situ growing boride and oxide nanoparticles on carbon fibers. Background Art
[0002] Ultra-high temperature ceramics (UHTC) refer to a class of ceramic compounds with a melting point of more than 3000°C, which can be used in extremely high temperatures and harsh chemical environments and maintain their performance stability. They are the most promising materials for manufacturing hypersonic aircraft. However, the brittleness of ceramic materials has become the biggest limitation for the application of ultra-high temperature ceramic materials. In order to overcome the brittleness of ceramic materials, ceramic fibers have attracted attention due to their high specific strength, high specific modulus, high temperature resistance and oxidation resistance. The preparation of fiber-reinforced composite materials can effectively solve the problems of ceramic brittleness and poor thermal shock resistance, and better meet the stringent requirements for materials in the fields of national defense, aerospace, etc.
[0003] At present, carbon fiber is widely used in the field of aerospace. It is a special fiber with high strength, high modulus, fatigue resistance, electrical conductivity and thermal conductivity. However, with the rapid development of aerospace technology, aircraft have been developing in the direction of higher speed, which also requires the corresponding materials to have higher high temperature resistance, corrosion resistance, oxidation resistance and thermal shock resistance. Obviously, the use of carbon fiber composite alone cannot meet these requirements.
[0004] The prior art improves the physical and chemical properties of carbon fiber by introducing boride nanoparticles into the carbon fiber. For example, Chinese invention patent publication number CN112144149A discloses a method for preparing a multilayer composite fiber of PAN-based carbon fiber coated with micron zirconium boride particles. The problems existing in the preparation method are mainly the uneven distribution of boride nanoparticles and the directly introduced micron-sized ceramic powder, which is not conducive to bringing into play the advantages of the composite fiber material. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the present invention provides a method for in-situ growth of boride and oxide nanoparticles on carbon fiber, which can not only make the boride and oxide nanoparticles evenly distributed on the carbon fiber, but also grow them in situ by direct carbon thermal reduction method, which has a simple principle and is easy to implement.
[0006] To achieve the above object, the present invention adopts the following technical solution: a method for in-situ growth of boride and oxide nanoparticles on carbon fiber, comprising the following steps:
[0007] Step S1, mixing sorbitol, boric acid and acetic acid, wherein the molar ratio of carbon contained in sorbitol to boron contained in boric acid is 10:6, and then adding ethanol and mixing and stirring until the solution is clear, to obtain a mixed solution A;
[0008] Step S2, dropping zirconium n-propoxide / hafnium n-propoxide into acetic acid, and stirring evenly to obtain a mixed solution B;
[0009] Step S3, mixing mixed solution A with mixed solution B, wherein the molar ratio of boron contained in boric acid and zirconium / hafnium contained in zirconium n-propoxide / hafnium n-propoxide in mixed solution A is 6:1, and stirring until clarified to obtain mixed solution C;
[0010] Step S4, adding ethanol to the mixed solution C for dilution and stirring, and then slowly adding polyvinyl pyrrolidone PVP, wherein the amount of PVP added to the mixed solution C before dilution is 6-10wt%, and stirring evenly, and then standing to degas, to obtain an electrospinning solution;
[0011] Step S5, spinning the electrospinning solution to obtain a precursor fiber membrane;
[0012] Step S6, drying the precursor fiber membrane, and then pre-oxidizing it at 300-400° C. for 2-4 hours;
[0013] Step S7, placing the pre-oxidation treated fiber membrane in a mixed gas of Ar and O2, and calcining at 1300-1600°C for 2-4h, thereby obtaining a composite fiber membrane with in-situ grown boride and oxide nanoparticles.
[0014] As a further improvement of the method for in situ growth of boride and oxide nanoparticles on carbon fibers:
[0015] Preferably, the operations of steps S1, S2 and S3 are carried out in a water bath at 60-80°C, with a stirring speed of 100-500 rpm and a time of 60-80 min.
[0016] Preferably, in step S1, the concentration of boric acid in the mixed solution A is 2.5-3 mol / L.
[0017] Preferably, the volume ratio of acetic acid to ethanol in step S1 is 1:(1.25-2).
[0018] Preferably, in step S2, the concentration of zirconium n-propoxide / hafnium n-propoxide added to acetic acid is 1-1.5 mol / L.
[0019] Preferably, the volume ratio of the total amount of ethanol added in steps S1 and S4 to the acetic acid used in step S1 is (2-2.5):1.
[0020] Preferably, the amount of PVP added to the mixed solution C before dilution in step S4 is 6-10 wt %.
[0021] Preferably, the manufacturer of the spinning equipment in step S5 is Hefei Kejing Material Technology Co., Ltd., the model is MSK-NFES-1U, and the specific parameters are set as follows: high voltage 15-18KV, spinning liquid propulsion speed 0.5-1ml / h, receiving distance 15-20cm, and collection speed 200-400rpm.
[0022] Preferably, the specific steps of drying the precursor fiber membrane in step S6 are as follows: first place it in an oven at 60-80° C. for 12-24 hours, and then transfer it to an oven at 120-150° C. for 12-24 hours.
[0023] Preferably, the volume fraction of oxygen in the Ar and O2 mixed gas in step S7 is 0-5% and not 0, and the gas flow rate of the mixed gas is 80-150 ml / min.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1) The present invention provides an electrospinning technology for in-situ growth of boride and oxide particles of zirconium / hafnium metal elements on carbon fiber by direct carbon thermal reduction. The specific method is as follows: an electrospinning solution is prepared using boric acid, sorbitol, zirconium n-propoxide / hafnium n-propoxide, and polyvinyl pyrrolidone as raw materials, and the fiber membrane is subsequently pre-oxidized and calcined under a mixed gas of argon and oxygen to obtain a fiber membrane with in-situ growth of boride and oxide ceramic particles on the carbon fiber with good morphology.
[0026] Boric acid and sorbitol are selected as the boron source and carbon source respectively, which can react to form a boron-containing six-membered ring and produce H + , H + It is beneficial to electrospinning. Acetic acid and ethanol are used as solvents, especially the addition of ethanol can increase the spinnability of the solution and improve the solid content of the spinning solution.
[0027] As a metal source, alkoxide first reacts with acetic acid, and acetic acid as a chelating agent can modify alkoxide to block its hydrolysis. The two solutions are mixed and reacted to form a stable Zr-O-Zr and Zr-OCB network, and the required zirconium oxide and zirconium boride are formed in the subsequent reaction. The added PVP is connected to the above network structure in the form of hydrogen bonds to form a stable and highly spinnable electrospinning solution. Considering that carbon needs to be retained as a skeleton in the end and the B source will volatilize at high temperatures, the material ratio is higher than the original ratio of the reaction. If pure argon is used during calcination, it will be difficult to retain carbon fibers when the temperature is continuously raised to the reaction temperature. Even if carbon fibers exist, the morphology will be uneven. Therefore, using an argon / oxygen mixed gas to introduce a portion of oxygen to form zirconium oxide will stabilize the carbon fiber structure and produce a certain amount of zirconium boride.
[0028] Water bath conditions can promote dissolution and reaction, and setting the stirring speed and time can increase the dispersibility of the raw materials.
[0029] 2) Borides and oxides of zirconium / hafnium metal elements are generally high thermal conductivity, high melting point, high hardness, good thermal shock resistance and chemical stability. Evenly distributing them on carbon fibers can improve the ablation resistance and oxidation resistance of carbon fibers, and can solve the problem of thermal expansion coefficient mismatch to a certain extent when compounded with boride ceramic powders, and also bring some potential applications. The preparation method of the present invention cleverly combines the strength, modulus, dimensional stability and photoelectric properties of boride and oxide ceramics with the toughness, processability and dielectric properties of carbon materials. Through electrostatic spinning, boride and oxide nanoparticles of zirconium / hafnium metal elements are introduced into the carbon network structure constructed by polyvinyl pyrrolidone (PVP), and the synergistic effect of the two is well exerted. In addition, since nanoparticles have a relatively large specific surface area, by introducing nanoparticles into carbon fibers, a very strong interface interaction is generated between the nanoparticles and the carbon fibers, which will produce unique mechanical, thermal, electromagnetic and optical properties. The preparation method is simple in principle and easy to implement. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0031] Figure 1 It is a schematic diagram of the preparation process of the present invention.
[0032] Figure 2 The XRD diagram of the composite fiber membrane finally prepared in Examples 1 and 2 of the present invention.
[0033] Figure 3 These are scanning electron microscope photographs of the as-spun precursor fiber with in-situ growth of zirconium boride and zirconium oxide particles on the carbon fiber prepared in Example 1 of the present invention and a scanning electron microscope photograph of the composite fiber after heat treatment.
[0034] Figure 4 These are scanning electron microscope photographs of the as-spun precursor fiber with in-situ growth of hafnium boride and hafnium oxide particles on the carbon fiber prepared in Example 2 of the present invention and a scanning electron microscope photograph of the composite fiber after heat treatment.
[0035] Figure 5 This is a transmission electron microscope photograph of zirconium boride and zirconium oxide particles grown in situ on the carbon fiber prepared in Example 1 of the present invention.
[0036] Figure 6 This is a transmission electron microscope photograph of hafnium boride and hafnium oxide particles grown in situ on the carbon fiber prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0038] Example 1
[0039] This embodiment provides a method for preparing zirconium boride and zirconium oxide particles grown in situ on carbon fibers. The preparation process is as follows: Figure 1 As shown, the specific steps include:
[0040] Step S11, in a water bath at 60° C., 6.2 g of boric acid, 5.5 g of sorbitol and 16 ml of acetic acid were mixed and stirred, the molar ratio of carbon contained in sorbitol to boron contained in boric acid being 10:6, and then 20 ml of ethanol was added and stirred until dissolved and clarified, the concentration of boric acid in mixed solution A was 2.8 mol / L, and mixed solution A was obtained;
[0041] Step S21, under a 60° C. water bath condition, dropwise add 7.5 ml of zirconium n-propoxide into 12 ml of acetic acid, wherein the concentration of zirconium n-propoxide in acetic acid is 1.4 mol / L, and stir to obtain a mixed solution B;
[0042] Step S31, adding mixed solution B to mixed solution A, wherein the molar ratio of boron introduced by boric acid in mixed solution A to zirconium introduced by zirconium n-propoxide in mixed solution B is 6:1, stirring in a water bath at 60° C. for 1 hour to obtain a clear mixed solution C, and cooling to room temperature for standby use;
[0043] Step S41, adding 15 ml of ethanol to the mixed solution C at room temperature for dilution and stirring, then slowly adding 2.09 g of polyvinyl pyrrolidone PVP, the concentration of PVP added to the mixed solution C before dilution is 7 wt %, stirring evenly and standing to degas, to obtain an electrospinning solution;
[0044] Step S51, double-needle spinning of the electrospinning solution, the equipment manufacturer is Hefei Kejing Material Technology Co., Ltd., the model is MSK-NFES-1U, the high voltage is set to 18KV, the propulsion speed is 0.5ml / h, the receiving distance is 15cm, the drum speed is 300rpm, and a precursor fiber membrane is obtained;
[0045] Step S61, placing the precursor fiber membrane in a 60°C oven for 12 hours, then transferring to a 150°C oven for 12 hours, and then heating to 350°C in a tube furnace at a heating rate of 2°C / min and keeping the temperature for 4 hours for pre-oxidation treatment;
[0046] Step S71, placing the pre-oxidation treated fiber membrane in a tubular furnace, introducing an Ar and O2 mixed gas with a gas flow rate of 100 ml / min, wherein the O2 volume fraction in the mixed gas is 1%, heating to 1350°C at a heating rate of 2°C / min and calcining for 4 hours, thereby obtaining a composite fiber membrane with in-situ grown zirconium boride and zirconium oxide nanoparticles.
[0047] Example 2
[0048] This embodiment provides a method for preparing hafnium boride and hafnium oxide particles grown in situ on carbon fiber. The preparation process is as follows: Figure 1 As shown, the specific steps include:
[0049] Step S12, in a water bath at 60° C., 6.2 g of boric acid, 5.5 g of sorbitol and 16 ml of acetic acid were mixed and stirred, wherein the molar ratio of carbon contained in sorbitol to boron contained in boric acid was 10:6, and then 20 ml of ethanol was added and mixed and stirred until dissolved and clarified, and the concentration of boric acid in mixed solution A was 2.8 mol / L, to obtain mixed solution A;
[0050] Step S22, under a 60° C. water bath condition, dropwise add 11.06 g of hafnium n-propoxide into 12 ml of acetic acid, wherein the concentration of hafnium n-propoxide in acetic acid is 1.3 mol / L, and stir to obtain a mixed solution B;
[0051] Step S32, adding mixed solution B to mixed solution A, wherein the molar ratio of boron introduced from boric acid in mixed solution A to zirconium introduced from zirconium n-propoxide in mixed solution B is 6:1, stirring in a water bath at 60° C. for 1 h to obtain a clear mixed solution C, and cooling to room temperature for standby use;
[0052] Step S42, adding 15 ml of ethanol to the mixed solution C at room temperature for dilution and stirring, then slowly adding 2.28 g of polyvinyl pyrrolidone PVP, the added concentration of PVP in the mixed solution C before dilution is 6.5 wt %, stirring evenly and standing for degassing to obtain an electrospinning solution;
[0053] Step S52, the electrospinning solution is subjected to double needle spinning, the equipment manufacturer is Hefei Kejing Material Technology Co., Ltd., the model is MSK-NFES-1U, the high voltage is set to 18KV, the propulsion speed is 0.5ml / h, the receiving distance is 15cm, the drum speed is 300rpm, and the initial spinning precursor fiber membrane is obtained;
[0054] Step S62, placing the precursor fiber membrane in a 60°C oven for 15 hours, then transferring to a 150°C oven for 15 hours, and then heating to 350°C in a tube furnace at a heating rate of 2°C / min and keeping the temperature for 4 hours for pre-oxidation treatment;
[0055] Step S72, placing the pre-oxidized fiber membrane in a tubular furnace, introducing an Ar and O2 mixed gas with a gas flow rate of 100 ml / min, in which the O2 volume fraction is 2%, heating it to 1400°C at a heating rate of 2°C / min and calcining it for 4 hours, thereby obtaining a composite fiber membrane with in-situ grown hafnium boride and hafnium oxide nanoparticles.
[0056] Morphology and phase detection
[0057] (1) The final fibers obtained in Example 1 and Example 2 of the present invention were measured by X-ray diffractometer. It can be found that the composite fiber membrane obtained in Example 1 is composed of zirconium boride, zirconium oxide and carbon. Figure 2 (a). The composite fiber membrane finally obtained in Example 2 is composed of hafnium boride, hafnium oxide and carbon, such as Figure 2 Middle (b).
[0058] (2) The initial spun precursor fibers and the composite fibers obtained after the heat treatment process prepared in Examples 1 and 2 of the present invention were observed using a scanning electron microscope. It can be seen that the initial spun precursor fibers of Example 1 have a diameter of approximately 200-300 nm, a smooth surface, and a good morphology. In the composite fibers after the heat treatment, zirconium boride particles are uniformly grown on the carbon fibers, and the particle diameter is approximately about 200 nm. Figure 3 Example 2: The diameter of the initial spun precursor fiber is approximately 500-600nm, the surface is smooth, and the morphology is good. After heat treatment, the composite fiber has hafnium boride particles uniformly grown on the carbon fiber, and the particle diameter is approximately 300-400nm. Figure 4 .
[0059] (3) Using a transmission electron microscope, the embodiments 1 and 2 of the present invention were observed to obtain the following: Figure 5 , 6 The transmission photograph shown. It can be seen that the microstructure of the zirconium boride grown in situ on the carbon fiber prepared in Example 1 of the present invention is granular, and the particle size is relatively uniform, about 200nm, and the zirconium oxide particles are scattered on the carbon fiber, and the particle size is extremely small, a few nanometers. From Picture 5, the composition of the substance can be further determined. From Picture 6, the microstructure of the hafnium boride and hafnium oxide grown in situ on the carbon fiber prepared in Example 2 of the present invention can be obtained. The particle size of the hafnium boride is relatively uniform, about 200nm, and the diameter of the hafnium oxide is about 4nm.
[0060] In summary, the embodiments of the present invention can make the boride and oxide nanoparticles of zirconium / hafnium uniformly distributed on the carbon fibers, and grow them in situ by direct carbon thermal reduction, which has a simple principle and is easy to implement.
[0061] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for in-situ growth of boride and oxide nanoparticles on carbon fiber, characterized in that: The following steps are involved: Step S1, mixing sorbitol, boric acid and acetic acid, wherein the molar ratio of carbon contained in sorbitol to boron contained in boric acid is 10:6, and then adding ethanol and mixing and stirring until the solution is clear to obtain a mixed solution A; wherein the concentration of boric acid in the mixed solution A is 2.5-3 mol / L, and the volume ratio of acetic acid to ethanol is 1:(1.25-2); Step S2, adding zirconium n-propoxide / hafnium n-propoxide dropwise into acetic acid at a concentration of 1-1.5 mol / L, and stirring to obtain a mixed solution B; Step S3, mixing mixed solution A with mixed solution B, wherein the molar ratio of boron contained in boric acid and zirconium / hafnium contained in zirconium n-propoxide / hafnium n-propoxide in mixed solution A is 6:1, and stirring until clarified to obtain mixed solution C; Step S4, adding ethanol to the mixed solution C for dilution and stirring, and then slowly adding polyvinyl pyrrolidone PVP, the amount of PVP added to the mixed solution C before dilution is 6-10wt%, stirring evenly and then standing to degas, to obtain an electrospinning solution; the volume ratio of the total amount of ethanol added in steps S1 and S4 to the acetic acid used in step S1 is (2-2.5):1; Step S5, spinning the electrospinning solution to obtain a precursor fiber membrane; Step S6, drying the precursor fiber membrane, and then pre-oxidizing it at 300-400° C. for 2-4 hours; Step S7, placing the pre-oxidized fiber membrane in a mixed gas of Ar and O2, wherein the oxygen volume fraction in the mixed gas is 0-5% and not 0, and calcining at 1300-1600°C for 2-4h, thereby obtaining a composite fiber membrane with in-situ grown boride and oxide nanoparticles.
2. A method for in-situ growth of boride and oxide nanoparticles on carbon fiber according to claim 1, characterized in that: The operations of steps S1, S2 and S3 are carried out in a water bath at 60-80°C, with a stirring speed of 100-500 rpm and a time of 60-80 min.
3. A method for in-situ growth of boride and oxide nanoparticles on carbon fiber according to claim 1, characterized in that: In step S4, the amount of PVP added to the mixed solution C before dilution is 7 wt %.
4. A method for in-situ growth of boride and oxide nanoparticles on carbon fiber according to claim 1, characterized in that: The model of the spinning equipment in step S5 is MSK-NFES-1U, and the specific parameters are set as follows: high voltage 15-18KV, spinning solution advancing speed 0.5-1ml / h, receiving distance 15-20cm, and collection speed 200-400rpm.
5. A method for in-situ growth of boride and oxide nanoparticles on carbon fiber according to claim 1, characterized in that: The specific steps of drying the precursor fiber membrane in step S6 are as follows: first place it in an oven at 60-80° C. for 12-24 hours, and then transfer it to an oven at 120-150° C. for 12-24 hours.
6. A method for in-situ growth of boride and oxide nanoparticles on carbon fiber according to claim 1, characterized in that: The gas flow rate of the mixed gas in step S7 is 80-150 ml / min.
Citation Information
Patent Citations
Preparation method of PAN-based carbon fiber coated micron zirconium boride particle multilayer composite fiber
CN112144149A
Preparation method for Co3O4-nanoparticle-loaded carbon fiber composite material and obtained product
CN105332097A
A nanosheet array nickel cobalt oxide-carbon composite material, a method for preparing the same and application of the same
CN108538611A
Method for preparing zirconium boride powder under assistance of alcohol solvent
CN111517799A